GENERASI MUDA DAN HAM: PERAN MAHASISWA DALAM MENJAGA HAK UNIVERSAL - Ahmad Arif Fadilah; Muhammad Luthfi; Wanda Adwi Kurnia (Cahaya Ilmu Bangsa, 2025)
The younger generation plays a very important role in maintaining and promoting human rights (HAM), which are the main pillars of a just and dignified life. This study aims to analyze the contribution of students as part of the younger generation in maintaining and fighting for universal rights in various aspects of life, both in the social, political, and cultural realms. Using a qualitative approach, this study applies a descriptive-analytical method. Data were collected through literature studies, in-depth interviews, and analysis of relevant documents, including national and international policies related to human rights. The research findings reveal that students act as agents of change through human rights advocacy, public education, and involvement in social movements that support the protection of the rights of minorities and vulnerable groups. Furthermore, students also have a moral responsibility to increase collective awareness of the importance of human rights, especially amidst global dynamics that often present challenges in the form of human rights violations and social injustice. Therefore, the implication of this study is the need to strengthen human rights education at the university level and the formation of human rights-based communities to optimize students’ contributions in creating an inclusive and just society. Thus, students as the younger generation have great potential to become pioneers of sustainable change in maintaining universal rights.